INTENSITAS DAN TIPE SERANGAN PENGGEREK KAYU DI PERAIRAN PULAU RAMBUT DAN PUNTUNG JAWA - Mohammad Muslich; Ginuk Sumarni (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
One hundred fifty pieces of wood consisting of 15 species were randomly arranged in form of a raft and floated at Rambut and Puntung Java Islands seashore. The size of the wood specimens is 2,5 cm x 5 cm x 30 cm. The samples were tested against two principal family of marine borers, i.e. teredinids and pholads and evaluated after three months. The results reveal that most of the tested woods were severely attacked by teredinids, except Heritiera littoralis, Heritiera javanica, Diospyros celebica, and Eucalyptus platyphylla, but these species were severely attacked by pholads. The infestation has two distinct types, characterited by its structure and pattern of wood boring